Betulinic Acid Decorated with Polar Groups and Blue Emitting BODIPY Dye: Synthesis, Cytotoxicity, Cell-Cycle Analysis and Anti-HIV Profiling - Kodr, David; Stanková, Jarmila; Rumlová, Michaela; Džubák, Petr; Řehulka, Jiří; Zimmermann, Tomáš; Křížová, Ivana; Gurská, Soňa; Hajdúch, Marián; Drašar, Pavel B; Jurášek, Michal (Biomedicines, 2021)
Betulinic acid (BA) is a potent triterpene, which has shown promising potential in cancer and HIV-1 treatment. Here, we report a synthesis and biological evaluation of 17 new compounds, including BODIPY labelled analogues derived from BA. The analogues terminated by amino moiety showed increased cytotoxicity (e.g., BA had on CCRF-CEM IC50 > 50 μM, amine 3 IC50 0.21 and amine 14 IC50 0.29). The cell-cycle arrest was evaluated and did not show general features for all the tested compounds. A fluorescence microscopy study of six derivatives revealed that only 4 and 6 were detected in living cells. These compounds were colocalized with the endoplasmic reticulum and mitochondria, indicating possible targets in these organelles. The study of anti-HIV-1 activity showed that 8, 10, 16, 17 and 18 have had IC50i > 10 μM. Only completely processed p24 CA was identified in the viruses formed in the presence of compounds 4 and 12. In the cases of 2, 8, 9, 10, 16, 17 and 18, we identified not fully processed p24 CA and p25 CA-SP1 protein. This observation suggests a similar mechanism of inhibition as described for bevirimat.
Keywords: cell-cycle; maturation inhibitor; bevirimat; betulinic acid; BODIPY; cytotoxicity; fluorescent microscopy; cancer